Green policy analysis: Communicating national strategy in addressing global environmental threats - Malik, Ichsan; Samudro, Eko G.; Maysarah, May May (Universitas Bunda Mulia, 2025)
Indonesia faces significant pressure from deforestation, climate change, and globalization, which exacerbate environmental vulnerabilities and threaten societal sustainability. An inclusive approach based on green policy is needed to integrate environmental protection, sustainable resource management, and strategic communication in addressing the complex challenges of global environmental threats. This study aims to analyze national green policy strategies in response to global environmental threats, focusing on three main aspects: (1) analyzing the impact of globalization on the environment, including changes in communication patterns in addressing environmental challenges; (2) examining the role of government communication in developing and implementing strategies to combat global warming; and (3) identifying the failures of international environmental regulations in addressing global issues and their impact on national security. This case study employs a qualitative method, involving the Indonesian Defense University and the Cultural Heritage Preservation Agency, with a total of 10 participants selected through purposive sampling. Data collection for this research was conducted through observation and documentation. The findings reveal that globalization significantly affects the environment through the exploitation of natural resources by multinational corporations and changes in communication patterns, which require the government to leverage digital technology to counter disinformation and enhance environmental awareness. Government communication plays a strategic role in formulating policies and mobilizing society to address global warming. Meanwhile, the failure of international regulations exacerbates the impact of climate change, increasing national security threats through resource conflicts and climate-induced migration. The effectiveness of national green policies depends on the integration of communication strategies, cultural value protection, and cross-sectoral coordination to holistically address global environmental challenges. This study provides an original contribution by combining local cultural approaches and national security strategies in green policy, an aspect that has been largely overlooked in previous research.